Корреляция в медицине - Mitrofanova M. N. (Student science in the XXI century, 2017)
Competent statistical processing of data - an integral part of modern medical science and practice. The author examines the process of identifying the correlation between the values that have biomedical significance.
Keywords: коэффициент корреляции; корреляция; correlation; статистическая обработка данных; медицинская статистика; correlation coefficient; statistical data processing; medical statistics